THE IMPACT OF MASS CUSTOMIZATION STRATEGIES ON USERS IN THE CONTEXT OF EXPRESSION, IDENTITY, AND SATISFACTION - Yunidar, Dandi; Siswanto, Riky Azharyandi (Universitas Telkom, 2023)
: The homogeneity of mass products often results in anonymity and detachment from the objects that surround our lives, resulting in an ever-increasing demand for products with diverse tastes, preferences, and personalities. This study aims to identify the impact of customization strategies on customers in terms of self- expression, personal identity, and satisfaction. Conducted within the framework of mass customization theory, this study employs qualitative analysis by applying phenomenological research methods, thereby enabling us to explore customer views and gather invaluable insights. Research findings reveal that customers value a structured, sequential approach to customization, where clarity of the process increases their engagement and satisfaction. In addition, the decision-making process serves as a symbol of individuality. Elements such as the ability to personalize products, a wide range of design options, and the inclusion of aesthetic appeal not only increase customer satisfaction but also emphasize the important role aesthetics plays in customization. The conclusions in this study recognize customization as a powerful tool for facilitating individual relationships and self-expression in the realm of mass commodities. Furthermore, this study adds to knowledge in the field of product development and marketing, with an emphasis on the importance of product customization for them. Keywords: Customization; self expression; personal identity; mass product; user satisfaction.